HISTORY AND DEVELOPMENT OF MAKAMA IN UZBEKISTAN (Ustozlar uchun, 2025)
The art of national makam, which is an integral part of the cultural heritage of our people, with its ancient history, deep philosophical roots, unique artistic style and rich creative traditions, plays an important role in our spiritual life according to history.